The Settlement of Non-Definite Loans through the Execution of Collateral Rights - Pertiwi, Tusi Wirahayu; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The objective of this study is to discover and analyze the Settlement of Bad Credit Through Executing Mortgage Guarantees at PT BPR Gunung Rizki in the city of Semarang, as well as to discover and analyze the obstacles faced in setting up bad loans through executing mortgage guarantees, as well as how to overcome the obstacles encountered in Settlement of bad debts through the execution of collateral rights. The research method used in this thesis is a sociological juridical legal research method, and the research specification employs descriptive analysis. The primary data used in this study is the 1945 Constitution, Act No. 4 of 1996, Mortgage law, Civil Code (KUHPerdata), Criminal Code (KUHP), and secondary data containing books and other supporting documents collecting research data by interview techniques and study of documents or library materials. The data analysis method used in this study is an interactive qualitative model as proposed by Miles and Huberman. The results of the study show that the settlement of bad loans through the execution of mortgage guarantees at the bank has procedures, terms and conditions from the time the debtor submits a credit application until the credit that has been given by the bank is paid off. Settlement of bad debts through the execution of mortgage guarantees is regulated in Act No. 4 of 1996 concerning the Mortgage Act (UUHT).Keywords: Credits; Execution; Guarantees; Mortgage; Right.